Charge-ordered phases in the hole-doped triangular Mott insulator 4 Hb - TaS2 - Bang, Junho; Lee, Byeongin; Yang, Hyungryul; Kim, Sunghun; Wulferding, Dirk; Cho, Doohee (Physical Review B, 2024)
4Hb-TaS2 has been proposed to possess unconventional superconductivity with broken time-reversal symmetry due to distinctive layered structure, featuring a heterojunction between a 2D triangular Mott insulator and a charge-density wave metal. However, since a frustrated spin state in the correlated insulating layer is susceptible to charge ordering with carrier doping, it is required to investigate the charge distribution driven by interlayer charge transfer to understand its superconductivity. Here, we use scanning-tunneling microscopy and spectroscopy (STM/S) to investigate the charge-ordered phases of 1T-TaS2 layers within 4Hb-TaS2, explicitly focusing on the non-half-filled regime. Our STS results show an energy gap which exhibits an out-of-phase relation with the charge density. We ascribe the competition between onsite and nonlocal Coulomb repulsion as the driving force for the charge-ordered insulating phase of a doped triangular Mott insulator. In addition, we discuss the role of the insulating layer in the enhanced superconductivity of 4Hb-TaS2.
Keywords: Broken time-reversal symmetry; Carrier doping; Charge-density-wave metals; Charge-ordered phase; Charge-ordering; Insulating layers; Layered Structures; Mott insulators; Spin state; Unconventional superconductivity